2023
DOI: 10.1021/acs.energyfuels.3c01273
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Mineral Impurities, Brine Ionic Composition and CO2 on Rock–Brine–Oil Electrokinetic Behavior Using a High-Salinity Surface Complexation Model

Abstract: ζ-Potential is applied in many subsurface processes including in the petroleum industry, deep saline aquifers, and geothermal fields to understand oil recovery, hydrogen, and CO2 storage. Typical subsurface formations contain high-salinity brine with multicomponent ionic species and varying mineral impurities. However, predicted ζ-potential models make use of surface complexation models (SCMs) compatible with low-salinity brine and/or single-salt brine and single mineral composition. In this study, a basic Ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(195 reference statements)
0
2
0
Order By: Relevance
“…In addition, the possible oil-brine interactions and their reaction constants have also been reported in literature [10,13,14]. Numerous developments have been made in recent years by several researchers to exploit these existing SCM data from literature to elucidate the mechanism during the experiment [22]. For example, zeta potential measurements have successfully been modeled via SCM [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the possible oil-brine interactions and their reaction constants have also been reported in literature [10,13,14]. Numerous developments have been made in recent years by several researchers to exploit these existing SCM data from literature to elucidate the mechanism during the experiment [22]. For example, zeta potential measurements have successfully been modeled via SCM [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous developments have been made in recent years by several researchers to exploit these existing SCM data from literature to elucidate the mechanism during the experiment [22]. For example, zeta potential measurements have successfully been modeled via SCM [22,23]. In addition, research has shown that the SCM technique is capable of modeling polymer interactions such as precipitation reactions at high surface coverage [24].…”
Section: Introductionmentioning
confidence: 99%